Investigating the Effect of Providence nighttime Brace on Correction of Scoliosis in Patients with Adolescent Idiopathic Scoliosis: A Review Study - Karami , Elahe; Daryabor, Aliyeh (Journal of Clinical Physiotherapy Research, 2020)
Introduction Scoliosis is a musculoskeletal disorder that can be treated by wearing full-time and part-time braces. It is not yet well understood whether part-time braces, such as Providence nighttime braces, are as effective as full-time braces in managing scoliotic curves. The aim of the present review study was to investigate the effect of Providence nighttime brace on correcting scoliosis in patients with adolescent idiopathic scoliosis (AIS). Methods: The search was performed using the keywords Scoliosis, Adolescent Idiopathic Scoliosis, Cobb angle, Nighttime Brace, Providence Brace, and Orthosis in PubMed, Science Direct, and ISI Web of Knowledge databases. Findings: A total of 10 relevant articles published between 2000 to December 2019 were selected for the final review according to the inclusion and exclusion criteria. Six articles investigated the effect of Providence brace before and after bracing treatment on the idiopathic scoliosis. Three articles compared the effect of Providence braces with full-time braces [Boston and Thoracic lumbar sacral Orthosis (TLSO)] on idiopathic scoliosis. One article also compared Providence brace with Charleston nighttime bending brace. Conclusion: Providence brace is an effective treatment approach to prevent the progression of scoliotic curves. However, it should be emphasized that its maximum effect is seen on the lumbar and thoracic curves< 35° with lower apex. Keywords: Cobb Angle; Nighttime; Providence Brace; Scoliosis